1988
DOI: 10.2307/3791319
|View full text |Cite
|
Sign up to set email alerts
|

Optimism about Elections: Dissonance Reduction at the Ballot Box

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.This field experiment investigated the effects of the act of voting itself on voters' attitudes in the 1984 presidential election. The subjects were 139 voters who were intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…"Wishful thinking" leads people to overestimate support for their favorite party and has been noticed in elections in the United States and elsewhere (Lazarsfeld et al ., 1944;Granberg and Brent, 1983;Granberg and Holmberg, 1988;Regan and Kilduff, 1988;Blais, 2002). Irwin and Van Holsteyn (2002) found that supporters of two parties whose performance would exceed the predictions of the polls were, consequently, more accurate in their predictions, while supporters of a party that did worse than the polls predicted appeared to be the most wishful.…”
Section: Literature Reviewmentioning
confidence: 94%
“…"Wishful thinking" leads people to overestimate support for their favorite party and has been noticed in elections in the United States and elsewhere (Lazarsfeld et al ., 1944;Granberg and Brent, 1983;Granberg and Holmberg, 1988;Regan and Kilduff, 1988;Blais, 2002). Irwin and Van Holsteyn (2002) found that supporters of two parties whose performance would exceed the predictions of the polls were, consequently, more accurate in their predictions, while supporters of a party that did worse than the polls predicted appeared to be the most wishful.…”
Section: Literature Reviewmentioning
confidence: 94%
“…For example, Frenkel and Doob (1976) recorded more favorable assessments and greater optimism concerning the electoral success of a preferred candidate among a sample of post-vote individuals compared to a similar sample queried prior to voting. Likewise, Regan and Kilduff (1988) interviewed voters entering and leaving polling locations during the 1984 presidential contest and found that voting raised assessments of the likelihood of victory for the favored candidate. In this fashion, the effect of behavioral commitment, independent of knowledge of the election outcome, has been shown to influence candidate evaluations.…”
Section: Choice-based Dissonancementioning
confidence: 99%
“…There is mixed evidence that WT is exacerbated by partisan intensity (Dolan and Holbrook ; Granberg and Brent ; Levine and Roberts ) and reduced by knowledge (Babad ; Dolan and Holbrook ; Sjöberg ). However, the act of voting is found to increase WT bias (Frenkel and Doob ; Regan and Kilduff ).…”
mentioning
confidence: 99%